1997
DOI: 10.1021/om960979q
|View full text |Cite
|
Sign up to set email alerts
|

Niobocene Alkyne Complexes:  Synthesis and Characterization of Neutral and Cationic d2Metal Alkyne Derivatives. X-ray Crystal Structure of [Nb(η5-C5H4SiMe3)22(C,C)-HC⋮CPh)(CH2Ph)]

Abstract: The paramagnetic niobocene alkyne complexes Nb(η5-C5H4SiMe3)2(η2(C,C)-RC⋮CR‘) (2) have been synthesized from Nb(η5-C5H4SiMe3)2(η2(C,C)-RC⋮CR‘)(Cl) (1) and subsequently oxidized in the presence of different ligands to give stable cationic d2 derivatives, [Nb(η5-C5H4SiMe3)2(η2(C,C)-RC⋮CR‘)(L)][BPh4] (L = CH3CN, R = R‘ = Ph (3a); L = CH3CN, R = R‘ = CO2Me (3b); L = CH3CN, R = R‘ = Me (3c); L = CH3CN, R = Me, R‘ = CO2Me (3d); L = tBuCN, R = R‘ = Ph (4a); L = tBuCN, R = R‘ = CO2Me (4b); L = tBuCN, R = R‘ = Me (4c);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…The second one, therefore, corresponds to the exo isomer, with the SiMe 3 group in the inside position with respect to the chloro atom, an arrangement sterically more hindered. We have previously reported several examples of this class of isomers in neutral haloketene and haloketenimine, and cationic ketenimine and alkyne complexes of niobocene, , in which the proportion of isomers was governed by steric factors, but this is the first time that the separation of both endo and exo isomers has proved possible. For complex 2b , only the thermodynamically favored endo isomer was observed, whereas a mixture of both isomers was isolated in the synthesis of the nonconjugated diyne-containing complex Nb(η 5 -C 5 H 4 SiMe 3 ) 2 Cl(η 2 ( C , C )-HC⋮CCH 2 CH 2 C⋮CH) ( 2c ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The second one, therefore, corresponds to the exo isomer, with the SiMe 3 group in the inside position with respect to the chloro atom, an arrangement sterically more hindered. We have previously reported several examples of this class of isomers in neutral haloketene and haloketenimine, and cationic ketenimine and alkyne complexes of niobocene, , in which the proportion of isomers was governed by steric factors, but this is the first time that the separation of both endo and exo isomers has proved possible. For complex 2b , only the thermodynamically favored endo isomer was observed, whereas a mixture of both isomers was isolated in the synthesis of the nonconjugated diyne-containing complex Nb(η 5 -C 5 H 4 SiMe 3 ) 2 Cl(η 2 ( C , C )-HC⋮CCH 2 CH 2 C⋮CH) ( 2c ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the reduction (Na/Hg) of 2b followed by treatment with BrCH 2 CHCH 2 , in pentane solution, led to a mixture of products from which the bromo derivative Nb(η 5 -C 5 H 4 SiMe 3 ) 2 Br(η 2 ( C , C )-PhC⋮CC⋮CPh) ( 2e ) was identified, indicating that the formation of the niobium(IV) species occurs in the reduction process. We recently showed that related Nb(IV) alkyne complexes undergo reactions with alkyl halides to give mixtures of alkyl−alkyne and halo−alkyne compounds, but in this case only the niobium halo−alkyne complex was observed 4f…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations